Family-oriented nursery approach to despair levels of the parents of children with cardiac disease and down syndrome - (:unkn) unknown (AVES PRESS LTD, 2015)
Objective: This experimental research was carried out in order to assess the effect of family oriented nursery approach to despair levels of the parents of children with cardiac disease and Down syndrome. Methods: The research was conducted with 77 parents having a child both with Down syndrome and cardiac disease in cardiology and cardiovascular surgery department or policlinics in a public hospital in Istanbul between March and May 2013:40 of them as experimental group and 37 others as research control group. In this study, 'family identification form' and 'Beck Desperation Scale' were used. Parents in the research group were trained through 'Education Booklet for Children with Down Syndrome' developed by the researcher. The data of the research were analyzed in computer environment. Regarding the data analysis; chi-square, t-test for the difference between two groups, and matched group t-test of for the comparison of repetitive measurements were used. Results: It is found out that before desperation point average (x +/- 8.37) of parents, who accept the central role of family concerning a child's life and care and were educated with family oriented approach, was higher than after desperation average (x +/- 4.10) leading a decrease in desperation (p<0.001). Before desperation point average for parents who didn't get education was lower (x +/- 8.75) than after desperation average (x +/- 11.37) leading an increase in desperation (p=0.006). Analyzing the desperation levels of parents who had family-oriented education, it was determined that the difference between desperation scores before and after education was statistically significant. Conclusion: The result of this study highlights the importance of family-oriented nursery approach in terms of parents who have a child with Down syndrome and cardiac disease dealing with despair.
Keywords: Family-oriented nursery; down syndrome; parent despair; child with cardiac disease; disabled